2014
DOI: 10.1210/en.2014-1020
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Prevents Podocyte Injury via Regulation of Macrophage M1/M2 Phenotype in Diabetic Nephropathy Rats

Abstract: Increasing evidence suggests the heterogeneity of macrophage phenotype and function ultimately determines the outcome of diabetic nephropathy (DN). This study aimed to investigate the effects of vitamin D on macrophage M1/M2 phenotype and its role in preventing podocyte impairment in streptozotocin-induced DN rats. Calcitriol, a bioactive 1,25-dihydroxyvitamin D3, ameliorated proteinuria and renal damage as well as reversed the decline of both nephrin and podocin, crucial structural proteins in podocytes. DN r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 45 publications
3
72
0
Order By: Relevance
“…The findings are principally in agreement with our data because retention of the NFκB subunits in the cytoplasma by prolonged binding to IκB-α subsequently destroys NFκB dimers [28]. Podocytes are apparently an important target of vitamin D3 and the hormone influences structure and function of podoyctes through various molecular mechanism [29,30,31,32]. In addition, activation of the NFκB-signaling pathway plays a major role in podocyte apoptosis [33,34,35], a pivotal feature of DN.…”
Section: Discussionsupporting
confidence: 89%
“…The findings are principally in agreement with our data because retention of the NFκB subunits in the cytoplasma by prolonged binding to IκB-α subsequently destroys NFκB dimers [28]. Podocytes are apparently an important target of vitamin D3 and the hormone influences structure and function of podoyctes through various molecular mechanism [29,30,31,32]. In addition, activation of the NFκB-signaling pathway plays a major role in podocyte apoptosis [33,34,35], a pivotal feature of DN.…”
Section: Discussionsupporting
confidence: 89%
“…In recent studies, increasing evidence demonstrated that the phenotype of the infiltrated macrophage was the major character that ultimately decided the sequelae of DN (27). M1 macrophages promote the inflammatory response and tissue injury, while the M2 macrophages provide the anti-inflammatory and tissue protective effects (28).…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages promote the inflammatory response and tissue injury, while the M2 macrophages provide the anti-inflammatory and tissue protective effects (28). The transformation of M1 phenotype could be initiated by pro-inflammatory cytokines such as IFN-y, and TNF-α, which in turn enhanced the secretion of these pro-inflammatory cytokines (27). In our experiment, iNOS, as the key M1 macrophage marker, was shown to estimate the population of activated macrophages and the severity of inflammation in DN models.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of 1,25(OH) 2 D 3 on M1/M2 polarization have recently been reported in studies in murine macrophages. In a rat model of diabetic nephropathy, 1,25(OH) 2 D 3 inhibited M1 macrophage activation, inflammation and renal injury while it enhanced M2 activation [26]. In another study, 1,25(OH) 2 D 3 suppressed high-glucose-induced M1 activation of rat macrophages while it enhanced M2 activation [27].…”
Section: Discussionmentioning
confidence: 99%